Pakistan Seed Dealer Survey - International Food Policy Research Institute; Innovative Development Strategies; National Institute of Genomics and Advanced Biotechnology, National Agricultural Research Center; University of Agriculture, Faisalabad (International Food Policy Research Institute, 2016)
The dataset "Seed Dealer Survey" was collected to inform the research study that examines the efficiency of markets for cotton seed in Pakistan with particular emphasis on the market for genetically modified cotton seed embodying insect-resistance traits from the soil bacterium Bacillus thurigiensis (Bt) that have been conferred through genetic modification. The purpose of the seed dealer survey and seed collection was to test the seed, through DNA fingerprinting, for purity and other traits (germination, moisture etc.). The survey was designed by the International Food Policy Research Institute (IFPRI) and implemented by Innovative Development Studies (IDS). The sample selection of seed dealers involved three steps: i) identification of markets from where most of the survey households in our sample for the study purchase seeds; ii) preparation of a list of all cotton seed dealers in these identified markets; and iii) selection of five seed dealers in each market and collect samples of three top selling varieties. The household survey identified that nearly 32 percent of the selected cotton growers purchased seeds from markets. These markets were located in 42 tehsils. Keeping in view the representation of all agroecological zones (AEZs) of cotton growing areas, 27 tehsil markets were randomly selected. A list of cotton seed dealers and cotton varieties that they purchased to sell in (kharif) 2015 were prepared in the selected tehsil markets. A cotton seed dealer is defined as a vendor of cotton seed. From the dealer listing, five seed dealers were selected randomly and subsequently top three selling cotton seed varieties per dealer were selected. In total, we had 135 seed dealers in our sample. A structured questionnaire was administered to collect information on the sale, purchase, and inventory of cotton seed varieties. Seeds of selected three cotton varieties were collected from each seed dealer. In total seeds of 404 cotton seed samples were collected. These samples were packed in bags and sent to the University of Agriculture, Faisalabad for DNA fingerprinting.